2021
DOI: 10.1098/rspa.2021.0408
|View full text |Cite
|
Sign up to set email alerts
|

A new integrable model of long wave–short wave interaction and linear stability spectra

Abstract: We consider the propagation of short waves which generate waves of much longer (infinite) wavelength. Model equations of such long wave–short wave (LS) resonant interaction, including integrable ones, are well known and have received much attention because of their appearance in various physical contexts, particularly fluid dynamics and plasma physics. Here we introduce a new LS integrable model which generalizes those first proposed by Yajima and Oikawa and by Newell. By means of its associated Lax pair, we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Models describing long wave-short wave resonant interactions arise in a variety of physical contexts, from fluid dynamics to plasma physics. In this paper, we consider the recently proposed, long wave-short wave YON (Yajima-Oikawa-Newell) model (see [11]), an integrable model featuring two arbitrary parameters, and unifying and generalizing the Yajima-Oikawa model and the Newell model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Models describing long wave-short wave resonant interactions arise in a variety of physical contexts, from fluid dynamics to plasma physics. In this paper, we consider the recently proposed, long wave-short wave YON (Yajima-Oikawa-Newell) model (see [11]), an integrable model featuring two arbitrary parameters, and unifying and generalizing the Yajima-Oikawa model and the Newell model.…”
Section: Discussionmentioning
confidence: 99%
“…In [11], it was shown that the YO and N Equations ( 1) and (2) need not be separately treated to investigate the short wave-long wave interaction. Indeed, these two different model equations, remarkably enough, can be combined in just one system, which we refer to as the YON model, that is itself integrable for any real value of the two arbitrary parameters α and β, namely…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The system (1) has been introduced in [36], where the authors have established the integrability of the above system by providing its (3 ⇥ 3) Lax Pair.…”
Section: Introductionmentioning
confidence: 99%